The Biological Evaluation of Jellyfish Collagen as a New Research Tool for the Growth and Culture of iPSC Derived Microglia - Mearns-Spragg, Andrew; Tilman, Jessica; Tams, Daniel; Barnes, Ashley (Frontiers in Marine Science, 2020)
Accurate disease models are essential for understanding disease pathogenesis and for developing new therapeutics. As stem cells are capable of self-renewal and differentiation, they are ideally suited both for generating these models and for obtaining the large quantities of cells required for drug development and transplantation therapies. Jellyfish collagen is showing great promise as a next generation matrix enabling improved outcomes in 2D and 3D cell culture and regenerative medicine. Here, we report the potential of jellyfish collagen for culturing induced pluripotent stem cell derived cell lines (iPSCs) for modelling human diseases. Jellyfish collagen from Rhizostomas pulmo (Jellagen®) was evaluated for the growth and viability of iPSC-derived microglial-like cells (iMGL) comparing to cells cultured on rat tail collagen 1, laminin-511 and tissue culture plastic. Viability was measured using MTT, XTT and Annexin V. Cell ramification was measured using Neurotracker software and ramification measured on the InCucyte S3TM. Cell surface receptor expression was quantified using flow cytometry. Microglia markers used for immunocytochemistry were IBA1, CD11b, TREM2, TMEM119 and P2RY12. We report that iPSC-derived microglia can be successfully cultured on Jellagen® jellyfish collagen demonstrating a more ramified cell morphology compared to cells cultured on mammalian rat tail collagen I and comparable to Laminin-511.